Assessment of the vegetation structure influence on bird communities’ occurrence in Iberian agro-forestry systems - Quinta-Nova, L.C. (2014)
The main objective of this study is to identify the structure/landscape measures having a greater influence on the presence of avian species in two types of agrossystems located in the South of Portugal. Four line transects were defined. Two were located in holm oak and cork oak “Montado" near Évora and the other in a pineyard located in the Setúbal Peninsula (Apostiça). Several variables were measured to describe the vegetation as a habitat. The linear transect technique was used in the bird sampling. Multivariate statistics were used to analyse the relation between the presence/absence of avian communities and the different vegetation cover measures. These include vegetation vertical structure and percentage of vegetation cover types. The relation between avian diversity and vegetation structure descriptors, as well as the vegetation diversity, was analysed using simple regression methods. The bird communities seem to respond to the above mentioned structural differences. Moreover, the diversity of these communities is related to the percent cover of shrub and tree layers.